Everyone deserves a great manager : the 6 critical practices for leading a team - Miller, Scott, 1960-; Davis, Todd (Chief people officer); Roos-Olsson, Victoria (Simon & Schuster, 2019)
"From the organizational experts at FranklinCovey, an essential guide to becoming the great manager every team deserves"--